Impact of sanctions on the Russian economy - Pak, Alena (2016)
The economic sanctions in connection with the Ukrainian crisis have been implemented in order to prevent the Russian Federation from interference and escalation of the situation. The main determinant of effectiveness of economic sanctions is costs that are inflicted by these measures. The goal of this thesis is to find out whether economic sanctions have had an impact on the Russian economy. Russia has been experiencing recession since 2014. One of causes is economic sanctions. Statistical analysis within the theory of gravity model of trade confirms that economic sanctions have had impact on the Russian economy. Calculation of economic cost for Russia and political success of economic sanctions requires a separate research.